Association of initial imaging modality and futile recanalization after thrombectomy. (27th October 2020) - Meinel, Thomas Raphael; Kaesmacher, Johannes; Mosimann, Pascal John; Seiffge, David; Jung, Simon; Mordasini, Pasquale; Arnold, Marcel; Goeldlin, Martina; Hajdu, Steven D.; Olivé-Gadea, Marta; Maegerlein, Christian; Costalat, Vincent; et al.
Abstract : Objective: To test the hypothesis that selection by initial imaging modality (MRI vs CT) is associated with rate of futile recanalizations (FRs) after mechanical thrombectomy (MT), we assessed this association in a multicenter, retrospective observational registry (BEYOND-SWIFT [Registry for Evaluating Outcome of Acute Ischemic Stroke Patients Treated With Mechanical Thrombectomy], NCT03496064). Methods: In 2, 011 patients (49.7% female, median age 73 years [61–81]) included between 2009 and 2017, we performed univariate and multivariate analyses regarding the occurrence of FR. FRs were defined as 90-day modified Rankin Scale (mRS) score 4–6 despite successful recanalization in patients selected by MRI (n = 690) and CT (n = 1, 321) with a sensitivity analysis considering only patients with mRS 5–6 as futile. Results: MRI as compared to CT resulted in similar rates of subsequent MT (adjusted odds ratio [aOR] 1.048, 95% confidence interval [CI] 0.677–1.624). Rates of FR were as follows: 571/1, 489 (38%) FR mRS 4–6 including 393/1, 489 (26%) FR mRS 5–6. CT-based selection was associated with increased rates of FRs compared to MRI (44% [41%–47%] vs 29% [25%–32%], p < 0.001; aOR 1.77 [95% CI 1.25–2.51]). These findings were robust in sensitivity analysis. MRI-selected patients had a delay of approximately 30 minutes in workflow metrics in real-world university comprehensive stroke centers. However, functional outcome and mortality were more favorable in patients selected by MRI compared to patients selected with CT. Conclusions: CT selection for MT was associated with an increased risk of FRs as compared to MRI selection. Efforts are needed to shorten workflow delays in MRI patients. Further research is needed to clarify the role of the initial imaging modality on FR occurrence and to develop a reliable FR prediction algorithm.